Engineering education 5.0: a systematic literature review on competence-based education in the industrial engineering and management discipline - Corina Pacher; Manuel Woschank; Bernd M. Zunk; Elke Gruber (Production and Manufacturing Research: An Open Access Journal)
The holistic integration of the human workforce in digital and sustainable manufacturing and logistics systems requires structured approaches for the systematic (re-)alignment of professional education initiatives. Engineering education is seen as a critical investment for the further development of industry and society. However, future engineers will require more than just a strong technological background. Empirical-based success factors that contribute to the holistic reorientation of engineering education are typically researched in a fragmented manner and the focus on competence-orientation is frequently overlooked, especially in the Industrial Engineering and Management (IEM) discipline. In this paper, the authors conduct a systematic literature review on engineering education with an emphasis on competence-based engineering education in the IEM discipline. Moreover, the authors provide fruitful implications for the competence-based realignment of engineering education, present an amalgamated overview of competences that are considered necessary for future engineering education, and provide a set of novel methods and tools.